Band gap tuning in MgGeN2 chalcopyrite with Sr and Sn doping: An ab-initio investigation. (15th June 2022) - Khan, Karina; Soni, Amit; Ahuja, Ushma; Sahariya, Jagrati
Abstract: In this paper, we have investigated the impact of mono and co-doping of Sr/Sn on the electronic, optical and structural properties of MgGeN2 . The effects of Sr/Sn doping at Mg/Ge site are investigated to explore the potential of pure and doped compounds in optoelectronic applications. For the investigations of electronic and optical properties such as, energy bands, density of states, dielectric tensors, absorption coefficient, reflectivity and refractivity spectra, of MgGeN2, Mg1-x Srx GeN2, MgGe1-x Snx N2 and Mg1-x Srx Ge1-x Snx N2 (x = 0.0625, 0.125) compounds, we have used the Perdew-Burke-Ernzerhof generalized gradient approximation potential and further ameliorated by Tran-Blaha modified Becke Johnson exchange co-relation potential. The stability of the doped compounds is discussed in terms of formation energy and binding energy for the mono and co-doped compounds. It is observed that the doping of Sr/Sn at Mg/Ge reduces the band gap of MgGeN2 . The energy gap of MgGeN2 reduces from 2.90 eV to 2.25 eV with 12.5% co-doping of Sr and Sn. The potential of pure and doped compounds for optoelectronic applications are discussed in terms of their optical properties. Highlights: Investigated Opto-electronic properties for pure, mono and co-doped MgGeN2 . Demonstrated the effect of doping on optoelectronic properties of MgGeN2 . Discussed the dielectric tensor in term of inter band transitions. Possibility of utilization in photovoltaic and optoelectronic is discussed.